Rethinking Black German studies approaches, interventions and histories - Florvil, Tiffany N. 1980-; Plumly, Vanessa D. (Peter Lang, 2018)
Black German Studies is an interdisciplinary field that has experienced significant growth over the past three decades, integrating subjects such as gender studies, diaspora studies, history, and media and performance studies. The field?s contextual roots as well as historical backdrop, nevertheless, span centuries. This volume assesses where the field is now by exploring the nuances of how the past ? colonial, Weimar, National Socialist, post-1945, and post-Wende ? informs the present and future of Black German Studies; how present generations of Black Germans look to those of the past for direction and empowerment; how discourses shift due to the diversification of power structures and the questioning of identity-based categories; and how Black Germans affirm their agency and cultural identity through cultural productions that engender both counter-discourses and counter-narratives.0Examining Black German Studies as a critical, hermeneutic field of inquiry, the contributions are organized around three thematically conceptualized sections: German and Austrian literature and history; pedagogy and theory; and art and performance. Presenting critical works in the fields of performance studies, communication and rhetoric, and musicology, the volume complicates traditional historical narratives, interrogates interdisciplinary methods, and introduces theoretical approaches that help to advance the field
Literaturangaben
Keywords: Geschichte; Kultur; Schwarze; Literatur; Deutsch; Musik; Deutschland; Österreich; Aufsatzsammlung